Cysteine residues in CUB-1 domain are critical for ADAMTS13 secretion and stability - Zhou, Zhou; Yeh, Hui-Chun; Jing, Hua; Wang, Christina; Tao, Zhenyin; Choi, Huiwan; Aboulfatova, Khatira; Li, Renhao; Dong, Jing-fei (Thrombosis and Haemostasis, 2011)
Upon stimulation, endothelial cells release von Willebrand factor (VWF) enriched in ultra-large (UL) forms that are rapidly cleaved by ADAMTS13. The zinc metalloprotease fits in the consensus for members of the ADAMTS family, but also contains two unique C-terminal CUB domains. There are five and two cysteine residues in the CUB-1 and CUB-2 domains, respectively, instead of four as deducted from the consensus. In this study, we investigated the role of cysteine residues in the CUB-1 domain in ADAMTS13 synthesis and activity. CUB-1 and cysteine mutations were expressed in mammalian cell lines and examined for synthesis, secretion, stability, and VWF-cleaving activity. When expressed as an isolated domain, CUB-1, but not CUB-2, covalently aggregated. Converting any of the four cysteines that fit in the CUB consensus (C1192, C1213, C1236 and C1254) reduced the secretion of the mutants to the conditioned medium, but not to extracellular matrix. The mutations also resulted in a moderate increase in proteolytic degradation and decrease in cleaving VWF under static, but not flowing conditions. In contrast, replacing C1275, which was found to be in the thiol form, with a serine residue prevented covalent aggregation of CUB-1, but had no effect on secretion and VWF-cleaving activity. C1275S was also markedly resistant to proteolytic degradation. The data illustrate the importance of consensus cysteines in the secretion and proteolytic activity of ADAMTS13. They also identify an ADAMTS-13 mutant that is resistant to proteolytic degradation, while maintaining a normal VWF-cleaving activity.
Keywords: TTP; ADAMTS13; CUB domains; cysteine; biosynthesis; stability